DETERMINAN PERTUMBUHAN ASET PADA PERUSAHAAN DAN UNIT USAHA ASURANSI JIWA SYARIAH DI INDONESIA - Shifa, Maylaffayza Permata; Fitri, Resfa; Alim, Ahmad Syahirul (Program Studi Manajemen Pembangunan Daerah. Fakultas Ekonomi dan Manajemen. IPB University, 2025)
Abstract. The average growth of Islamic life insurance assets 2018-2023 is 2,82%, much lower than the average growth of conventional life insurance assets of 14,62%. Low asset growth in Islamic life insurance companies can lead to various risks, including difficulties in fulfilling obligations. This study aims to look at the effect of investment returns, tabarru’ funds, contributions, claims, and return on assets on the asset growth of the Islamic life insurance industry in Indonesia during the 2018-2023 period. The data used is data sourced from the annual financial statements of each company and business unit. This study uses panel data regression analysis with the help of Eviews software. The results showed that simultaneously all variables together had a significant effect on asset growth. Tabarru’ funds and contributions partially have a significant effect on asset growth while the variable investment returns, claims, and return on assets have no significant effect on the growth of Islamic life insurance assets in Indonesia. Key words: Asset growth, panel data regression, return on asset, sharia life insurance, tabarru’ funds